Catalyst for preparing gamma-butyrolactone through hydrogenation of dimethyl maleate as well as preparation method and application of catalyst

By preparing a core-shell structure catalyst, the problems of catalyst coking and insufficient activity during the hydrogenation of dimethyl maleate were solved, the production of γ-butyrolactone with high selectivity and stability was achieved, and the catalyst life was extended.

CN120618536APending Publication Date: 2025-09-12CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410276353.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

In the process of hydrogenating dimethyl maleate to γ-butyrolactone, the existing catalysts do not completely hydrogenate C=C and C=O, which easily generates by-products, leading to catalyst coking and deactivation, reducing selectivity and conversion rate. In addition, the catalyst strength and bulk density are insufficient, affecting the reaction stability.

Method used

A core-shell structure catalyst is used, with the core being Cu-AO and the shell being MO-B. A high-strength shell is formed through high-speed centrifugal granulation and silicate cement powder coating, which improves the bulk density and mechanical strength of the catalyst and ensures the smooth progress of the two-step hydrogenation reaction.

Benefits of technology

The selectivity and yield of gamma-butyrolactone are improved, the operating life of the catalyst is extended, catalyst coking is avoided, and the stability and activity of the reaction are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004735951170000151
    Figure BDA0004735951170000151
  • Figure BDA0004735951170000161
    Figure BDA0004735951170000161
  • Figure BDA0004735951170000162
    Figure BDA0004735951170000162
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing gamma-butyrolactone through dimethyl maleate hydrogenation as well as a preparation method and application of the catalyst. The catalyst is of a core-shell structure, the core is Cu-A-O, the shell is MO-B, A is an auxiliary agent and is selected from one or more of Zn, Mn, Ba, Mg, Ti, Ge, Zr and Cr; m is an active metal component and is selected from one or more of Pd, Ni, Pt, Au and Ag; and B is a carrier component. The catalyst is used in the process of preparing gamma-butyrolactone through dimethyl maleate hydrogenation, the conversion rate and gamma-butyrolactone selectivity can be improved, catalyst coking can be avoided, and the operation life of the catalyst is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst for preparing gamma-butyrolactone by hydrogenating dimethyl maleate, a preparation method thereof and application thereof in preparing gamma-butyrolactone by hydrogenating dimethyl maleate. Background Art

[0002] γ-Butyrolactone (GBL) is an important fine chemical intermediate. The reaction of GBL with aqueous methylamine is the only technical route for producing N-methylpyrrolidone (NMP). With the continuous expansion of electric vehicle production capacity, NMP continues to gain popularity in the lithium battery field, creating a huge demand for GBL raw materials. Maleic anhydride esterification and hydrogenation technology is a key technology for GBL production. The hydrogenation of dimethyl maleate to produce GBL is a two-step hydrogenation reaction. The first step is the rapid hydrogenation of the carbon-carbon double bond of dimethyl maleate over the action of a catalyst to produce dimethyl succinate; the second step is the hydrogenation of the ester group of dimethyl succinate to form γ-butyrolactone. Currently, most two-step hydrogenation reactions of dimethyl maleate use the same catalyst for both C=C hydrogenation and C=O hydrogenation.

[0003] CN113731442A discloses a catalyst for the hydrogenation of dimethyl maleate, its preparation method, and its application. The molar percentages of the elements in the catalyst are: Cu 30-40%, Mn 20-30%, Al 10-20%, Zn 10-20%, Ag 0-5%, and Ru 0-5%. By adding Al, Ag, and Ru to the catalyst, the active components are dispersed and modified, achieving a combined selectivity of 93% for 1,4-butanediol (BDO) and γ-butyrolactone.

[0004] CN113731442A discloses a chromium-free catalyst comprising a composite oxide composed of Cu, Mn, and Al. The catalyst has the following general formula: CuMn a Al b O c , where a = 0.01 to 1.5, preferably 0.04 to 1.0, b = 0.1 to 2, preferably 0.2 to 1.5, and c is the number of oxygen atoms that meets the valence requirements of other elements. When the reaction temperature is 170°C to 300°C, the pressure is 0.1 to 7.0 MPa, and the space velocity of the ester is 0.1 to 15 h -1 , and a hydrogenation reaction is carried out under the condition of a hydrogen / ester molar ratio of 5 to 250:1 to produce γ-butyrolactone.

[0005] CN1646514A discloses a method for preparing gamma-butyrolactone optionally substituted with a C₂ alkyl group by catalytic hydrogenation of maleic acid and / or its derivatives in the presence of a chromium-free catalyst. The chromium-free catalyst comprises 10 to 80% by weight of copper monoxide and 10 to 90% by weight of at least one catalyst support selected from silicon dioxide, titanium dioxide, zirconium dioxide, magnesium silicate, activated carbon, silicon carbide, zirconium dioxide, and aluminum oxide.

[0006] The two-step hydrogenation in the hydrogenation of dimethyl maleate involves two main hydrogenation reactions. Therefore, the catalyst uses the same active metal for the step-by-step hydrogenation of C=C and C=O. During the reaction, the hydrogenation of C=C and C=O is prone to incomplete, generating olefins or aldehydes as byproducts. These byproducts can self-polymerize or polymerize with the product γ-butyrolactone at the reaction temperature, adhering to the catalyst surface and causing coking and deactivation of the catalyst, reducing the catalyst's selectivity and conversion rate for the target product, and thus hindering product production. Summary of the Invention

[0007] To address the shortcomings of the prior art, the present invention provides a catalyst for hydrogenating dimethyl maleate to produce γ-butyrolactone, as well as its preparation method and application. The catalyst of the present invention is used in the process of hydrogenating dimethyl maleate to produce γ-butyrolactone, improving conversion and γ-butyrolactone selectivity, while also preventing catalyst coking and extending catalyst life.

[0008] The inventors discovered that the hydrogenation of dimethyl maleate to γ-butyrolactone involves a two-step hydrogenation process. The first step involves the hydrogenation of the two C=C double bonds in dimethyl maleate. This reaction is highly exothermic and requires a catalyst with a stable active metal to prevent melting and sintering of the exothermic active metal. The second step involves the hydrogenation of the C=O double bond in dimethyl succinate. This reaction requires a catalyst with adsorption capacity for the C=O double bond, allowing the hydrogenated product to rapidly adsorb to the active metal. Further research has revealed that core-shell catalysts containing different active metals can accomplish this two-step hydrogenation reaction by allowing the reactants to diffuse from the shell to the core. However, the dimethyl maleate hydrogenation reaction system requires materials with high bulk density and strength to enhance catalyst reactivity and bed stability. However, current methods for preparing core-shell catalysts are not suitable for preparing high bulk density and high strength dimethyl maleate hydrogenation catalysts.

[0009] The first aspect of the present invention provides a catalyst for hydrogenating dimethyl maleate to produce γ-butyrolactone. The catalyst has a core-shell structure, wherein the core is Cu-AO and the shell is MO-B, wherein A is an additive selected from one or more of Zn, Mn, Ba, Mg, Ti, Ge, Zr, and Cr; M is an active metal component selected from one or more of Pd, Ni, Pt, Au, and Ag; and B is a carrier component.

[0010] Furthermore, the bulk density of the catalyst is 100-150 kg / L, preferably 120-150 kg / L.

[0011] Furthermore, the mechanical strength of the catalyst is 80 to 150 N / particle, preferably 105 to 150 N / particle, and more preferably 110 to 150 N / particle.

[0012] Furthermore, the specific surface area of ​​the catalyst is 30 to 50 m 2 / g, the pore volume is 0.09~0.30ml / g, and the average pore diameter is 8~25nm.

[0013] Furthermore, the catalyst is in the form of spherical particles with a particle size of 0.5 to 7.0 mm, preferably 0.8 to 3.5 mm.

[0014] Furthermore, in the catalyst, the shell thickness accounts for 5% to 30% of the catalyst particle radius, preferably 10% to 15%.

[0015] Furthermore, in the catalyst, the core is Cu-AO, and A, calculated as oxide, accounts for 10% to 70% of the mass of Cu, calculated as oxide, preferably 30% to 50%.

[0016] Furthermore, in the catalyst, the shell is MO-B, and M accounts for 0.1% to 2.0% of the mass of B as an oxide, preferably 0.5% to 1.0%.

[0017] Furthermore, in the catalyst, B is a carrier component, preferably selected from one or more of alumina, activated carbon, and silica. The pore size of the carrier component is 10 to 40 nm, preferably 13 to 25 nm.

[0018] A second aspect of the present invention provides a method for preparing the above catalyst, comprising:

[0019] (1) Mixing the core raw material powder and the first binder into a wet ball,

[0020] (2) mixing the shell raw material powder with the second binder and coating the wet ball obtained in step (1);

[0021] (3) The material obtained in step (2) is allowed to stand in the presence of water vapor, and then dried and calcined to obtain a catalyst.

[0022] Furthermore, in step (1), the particle size of the core raw material powder is 60 mesh to 200 mesh.

[0023] Furthermore, in step (1), the core raw material powder includes CuO and an additive oxide, and the first binder is polyvinyl alcohol. The first binder is added in the form of an aqueous solution in an amount sufficient to enable the core raw material to be spherical. Generally, the concentration of the polyvinyl alcohol aqueous solution is 10% to 60%, and the amount of polyvinyl alcohol added accounts for 5% to 30% of the mass of the core raw material powder.

[0024] Furthermore, the pelletizing method in step (1) can be high-speed centrifugal granulation using a powerful mixer, with a rotation speed of 1000-3000 rpm, preferably 2000-2500 rpm; and a centrifugal time of 5-20 minutes, preferably 10-15 minutes.

[0025] Furthermore, the particle size of the wet bulb obtained in step (1) is 0.5 to 5.0 mm.

[0026] Furthermore, in step (2), the particle size of the shell raw material powder is 150 to 300 meshes.

[0027] Furthermore, in step (2), the shell raw material powder includes active metal oxide and carrier component, and the second binder is silicate cement powder. The amount of the second binder added accounts for 10% to 40% of the mass of the shell raw material powder.

[0028] Furthermore, in step (2), the coating method can be a rolling ball method.

[0029] Furthermore, in step (2), the coating thickness is 0.2 to 1.0 mm.

[0030] Furthermore, in step (3), the material obtained in step (2) is allowed to stand in the presence of water vapor under the following conditions: temperature of 100-150° C., preferably 120-130° C.; pressure of 0.3-0.8 MPa; and time of 1-10 hours, preferably 3-6 hours.

[0031] Furthermore, in step (3), the drying conditions are as follows: drying temperature is 80-120° C., and drying time is 4-10 h.

[0032] Furthermore, in step (3), the roasting conditions are as follows: the roasting temperature is 300-700° C., and the roasting time is 3-8 hours.

[0033] The third aspect of the present invention provides the use of the above catalyst in the hydrogenation of dimethyl maleate to γ-butyrolactone.

[0034] Furthermore, the application process is as follows: dimethyl maleate is contacted with the catalyst in the presence of hydrogen to react to obtain the product γ-butyrolactone.

[0035] Furthermore, the reaction conditions are as follows: reaction temperature is 200-240°C, reaction pressure is 1.0-7.0 MPa, hydrogen ester molar ratio is 100-500:1, liquid hourly volume space velocity is 0.1-1.0h -1 .

[0036] Furthermore, preferably, the yield of γ-butyrolactone is above 90%, preferably above 92%, and the yield of γ-butyrolactone and 1,4-butanediol is above 93%, preferably above 95%. Further preferably, when the operation is continued for 500 h, the yield of γ-butyrolactone is above 90%, preferably above 92%, and the yield of γ-butyrolactone and 1,4-butanediol is above 93%, preferably above 95%.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1. The catalyst of the present invention has Cu-AO as the core and MO-B as the shell, and has good bulk density and strength. It can not only realize the two-step hydrogenation reaction, but also has good activity and selectivity, as well as good stability.

[0039] 2. In the preparation method of the catalyst of the present invention, a high-strength core structure is obtained by high-speed centrifugal granulation in the first step. Then, by using silicate cement powder as a binder and steam curing, the core structure can further enhance its strength, so that the core-shell structure catalyst has high strength and bulk density, avoiding the generation of acidic products after the catalyst is loaded into the reactor, which causes a decrease in catalyst strength and an increase in reaction pressure drop, resulting in failure of the entire reaction system. At the same time, it also has good activity, selectivity and stability. DETAILED DESCRIPTION

[0040] The present invention is described in detail below with reference to the embodiments.

[0041] In the present invention, the metal ion is determined by stirring 60 mL of acetic acid (concentration of 10 wt%) and 5 g of catalyst powder at room temperature for 30 minutes, then separating the solution, filtering and washing, and quantitatively analyzing the metal ion content in the solution by the ICP method.

[0042] In the present invention, the specific surface area, pore volume and pore diameter are measured using the low-temperature liquid nitrogen adsorption (BET) method.

[0043] In the present invention, the bulk density is measured using a VIBRATOR-2 mechanical oscillator manufactured by Tianjin Aixin Medical Equipment Co., Ltd., an AL204 electronic balance manufactured by Mettler-Toledo Instruments (Shanghai) Co., Ltd., and a 250 mL graduated cylinder.

[0044] In the present invention, the mechanical strength of the catalyst carrier was measured using a DLIII intelligent particle strength instrument from the Dalian Research and Design Institute of Chemical Industry. The instrument had a range of 300 N and an accuracy of 0.1 N. Twenty samples were selected from the test sample, and the radial crushing force was measured. The maximum and minimum values ​​were removed, and the average value was taken as the mechanical strength of the catalyst.

[0045] The activity of the catalyst provided by the present invention can be evaluated by the following method:

[0046] The catalyst activity was evaluated in a micro fixed bed reactor. The calcined catalyst was placed in the micro reactor tube and activated with diluted H2 gas under the following conditions: pressurized to 2 MPa, and activated with hydrogen (volume space velocity 100 h -1 The catalyst was activated at 230°C for 10 hours. The raw material dimethyl maleate was pumped into the reaction tube as the reaction liquid through a feed pump, and then the reaction was carried out under pressure and at elevated temperature.

[0047] Example 1

[0048] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2·3H2O and 40 g of Zn(NO3)2·6H2O and a precipitant, aqueous ammonia (molar concentration of 3.52 mol / L), were added dropwise to form a coprecipitate. The pH of the precipitation system was maintained at 5.8, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 h, then calcined at 600°C for 4 h, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 2500 rpm. After granulation for 15 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0049] (2) 6 mL of a 20 mg / mL PdCl₂ solution was impregnated into 20 g of activated carbon (pore size 25 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet ball was gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0050] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 120°C, a time of 5 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide was 0.6%, and the mass of Zn in the core layer as ZnO accounted for 50% of the mass of Cu as CuO.

[0051] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0052] Example 2

[0053] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2 and 30 g of Mn(NO3)2 and a precipitant, sodium carbonate (molar concentration of 2.5 mol / L), were added dropwise to the solution for co-precipitation. The pH of the precipitation system was maintained at 6, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 h, then calcined at 600°C for 4 h, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 2500 rpm. After granulation for 15 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0054] (2) 6 mL of a 20 mg / mL PdCl₂ solution was impregnated into 20 g of activated carbon (pore size 25 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet ball was gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0055] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 120°C, a time of 5 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide was 0.6%, and the mass content of Mn in the core layer as MnO was 30% of the mass of Cu as CuO.

[0056] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0057] Example 3

[0058] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2·3H2O and 110 g of Mg(NO3)2·6H2O and a precipitant, sodium carbonate (molar concentration of 3 mol / L), were added dropwise to form a coprecipitation solution. The pH of the precipitation system was maintained at 5.8, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 h, then calcined at 600°C for 4 h, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 2500 rpm. After granulation for 15 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0059] (2) 2 mL of a 20 mg / mL PdCl₂ solution was impregnated into 6 g of activated carbon (pore size 25 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet ball was gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0060] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 120°C, a time of 5 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide is 0.2%, and the mass content of Mg in the core layer as MgO is 50% of the mass of Cu as CuO.

[0061] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0062] Example 4

[0063] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO₃)₂·3H₂O and 25 g of chromic anhydride and a precipitant, sodium carbonate (molar concentration of 3 mol / L), were added dropwise to form a coprecipitation solution. The pH of the precipitation system was maintained at 5.8, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 h, then calcined at 600°C for 4 h, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 2500 rpm. After granulation for 15 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0064] (2) 6 mL of a 20 mg / mL PdCl₂ solution was impregnated into 20 g of activated carbon (pore size 25 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet ball was gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0065] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 120°C, a time of 5 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide was 0.6%, and the mass content of Cr in the core layer as Cr2O3 accounted for 50% of the mass of Cu as CuO.

[0066] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0067] Example 5

[0068] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2 and 40 g of Zn(NO3)2 and a precipitant, aqueous ammonia (molar concentration of 3.52 mol / L), were added dropwise to form a coprecipitate. The pH of the precipitation system was maintained at 5.8, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 hours, then calcined at 600°C for 4 hours, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 2500 rpm. After granulation for 15 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0069] (2) 6 mL of a 20 mg / mL PdCl₂ solution was impregnated into 20 g of alumina (pore size 15 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet ball was gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0070] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 120°C, a time of 5 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide was 0.6%, and the mass of Zn in the core layer as ZnO accounted for 50% of the mass of Cu as CuO.

[0071] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0072] Example 6

[0073] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2 and 40 g of Zn(NO3)2 and a precipitant, aqueous ammonia (molar concentration of 3.52 mol / L), were added dropwise to form a coprecipitate. The pH of the precipitation system was maintained at 5.8, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 hours, then calcined at 600°C for 4 hours, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 2500 rpm. After granulation for 15 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0074] (2) 6 mL of a 20 mg / mL PdCl₂ solution was impregnated into 20 g of silica (pore size 12 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet spheres were gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0075] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 120°C, a time of 5 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide was 0.6%, and the mass of Zn in the core layer as ZnO accounted for 50% of the mass of Cu as CuO.

[0076] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0077] Example 7

[0078] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2 and 40 g of Zn(NO3)2 and a precipitant, aqueous ammonia (molar concentration of 3.52 mol / L), were added dropwise to form a coprecipitate. The pH of the precipitation system was maintained at 5.8, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 hours, then calcined at 600°C for 4 hours, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 1000 rpm. After granulation for 5 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0079] (2) 6 mL of a 20 mg / mL PdCl₂ solution was impregnated into 20 g of activated carbon (pore size 25 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet ball was gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0080] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 120°C, a time of 5 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide was 0.6%, and the mass of Zn in the core layer as ZnO accounted for 50% of the mass of Cu as CuO.

[0081] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0082] Example 8

[0083] (1) At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2 and 40 g of Zn(NO3)2 and a precipitant, aqueous ammonia (molar concentration of 3.52 mol / L), were added dropwise to form a coprecipitate. The pH of the precipitation system was maintained at 5.8, and constant temperature stirring was continued for 60 minutes after the addition was completed. The slurry was filtered, the resulting product was dried at 120°C for 6 hours, then calcined at 600°C for 4 hours, and pulverized in an 80-mesh oscillating granulator to obtain a core raw material powder. The core raw material powder was added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration of 20%) was added for mixing and granulation. The PVA addition amount was 20 g, and the centrifugal speed of the granulator was 2500 rpm. After granulation for 15 minutes, wet balls with a particle size of approximately 3 mm were obtained.

[0084] (2) 6 mL of a 20 mg / mL PdCl₂ solution was impregnated into 20 g of activated carbon (pore size 25 nm) and dried at 110°C for 4 h to obtain a shell raw material powder. The shell raw material powder was then mixed evenly with 2 g of Portland cement powder and gradually added to a high-pressure mixer equipped with the above-mentioned mixer. The wet ball was gradually coated with the second raw material powder to form a 0.2 mm shell layer.

[0085] (3) The obtained core-shell structured wet bulbs were first placed in a steam generator for curing at a temperature of 100°C, a time of 2 hours, and a pressure of 0.5 MPa; the cured small balls were placed in an oven and dried at 110°C for 6 hours; the dried product was calcined at 700°C for 5 hours to obtain a catalyst; wherein the mass content of Pd in ​​the shell layer as oxide was 0.6%, and the mass of Zn in the core layer as ZnO accounted for 50% of the mass of Cu as CuO.

[0086] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0087] Comparative Example 1

[0088] At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO₃)₂, 40 g of Zn(NO₃)₂·6H₂O, and 0.12 g of PdCl₂ was co-precipitated dropwise with a precipitant, aqueous ammonia (molar concentration of 3.52 mol / L). The pH of the precipitation system was maintained at 5.8. After the addition was complete, 20 g of activated carbon was gradually added, and the mixture was stirred at this constant temperature for 60 minutes. The slurry was filtered, dried at 120°C for 6 hours, calcined at 600°C for 4 hours, and pulverized in an 80-mesh oscillating granulator to obtain a catalyst powder. The resulting catalyst powder was tableted and granulated into cylindrical particles with a diameter and height of 3 mm. In the catalyst, the weight of Zn (calculated as ZnO) accounted for 50% of the weight of Cu (calculated as CuO).

[0089] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 5.

[0090] Comparative Example 2

[0091] At 60°C, 1000 mL of a mixed solution containing 100 g of Cu(NO3)2·3H2O and 40 g of Zn(NO3)2·6H2O and a precipitant ammonia water (molar concentration of 3.52 mol / L) were added dropwise in parallel for co-precipitation, and the pH value of the precipitation system was maintained at 5.8. After the addition was completed, constant temperature stirring was continued for 60 minutes; the product obtained after filtering the slurry was dried at 120°C for 6 hours, and then calcined at 600°C for 4 hours. After pulverization in an 80-mesh swing granulator, the core raw material powder was obtained. The core raw material powder is added to a high-pressure mixer, and a PVA binder aqueous solution (mass concentration is 20%) is added for mixing and granulation. The PVA addition amount is 20g, the centrifugal speed of the granulator is 2500rpm, and after 15 minutes of granulation, a wet bulb with a particle size of about 3mm is obtained; the obtained wet bulb is dried at 110°C for 6 hours; the dried product is calcined at 700°C for 5 hours to obtain a catalyst; Zn calculated as ZnO accounts for 50% of the mass of Cu calculated as CuO.

[0092] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 5.

[0093] Comparative Example 3

[0094] 6 mL of a prepared 20 mg / mL PdCl2 solution was impregnated into 20 g of activated carbon (pore size 25 nm) and dried at 110°C for 4 hours to obtain a shell raw material powder. The shell raw material powder was evenly mixed with 2 g of silicate cement powder and gradually added to the above-mentioned high-pressure mixer, gradually coating the wet bulb with the second raw material powder to form a 0.2 mm shell layer. The obtained wet bulb was first placed in a steam generator for curing at a temperature of 120°C for 5 hours and a pressure of 0.5 MPa. The cured pellets were placed in an oven and dried at 110°C for 6 hours. The dried product was then calcined at 700°C for 5 hours to obtain a catalyst; the mass content of Pd as oxide was 0.6%.

[0095] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 5.

[0096] Comparative Example 4

[0097] First, the hexadecyltrimethylammonium bromide (CTAB) template is used to hydrothermally synthesize the mercerized molecular sieve raw powder, which is then converted into hydrogen-type mercerized molecular sieve raw powder after H ion exchange, and then formed into The beads are then pre-adsorbed on the mercerized molecular sieve pores by pyridine gas and methyl iodide gas. The pyridine gas pretreatment temperature is 280°C, and the methyl iodide gas pretreatment temperature is 250°C.

[0098] Dissolve TEOS in water to form a colloid that is coated on the molecular sieve spheres, and then vacuum dry (drying temperature controlled at 50°C) to form a silica sol shell with a thickness of about 0.4 mm.

[0099] Ammonia solution of copper salt was sprayed on the silica sol shell, dried and then calcined in nitrogen gas at a temperature of 280°C. The Cu loading was 4.6 wt%.

[0100] Then, aluminum sol is coated on the Cu-based shell of the sphere and vacuum dried to form an aluminum sol shell. The drying temperature is controlled between 65°C and the aluminum sol coating thickness is 0.3mm.

[0101] An ammonia solution of copper salt was sprayed on the aluminum sol shell, dried, and calcined in a hydrogen atmosphere at 255°C to finally obtain a double Cu-based shell MOR core catalyst named CuAlQCuSiQMOR-1 with a Cu loading of 3.5 wt%.

[0102] The obtained catalyst was sieved through a 14-mesh sieve and then loaded into a microreactor for activity evaluation. The evaluation conditions are shown in Table 3, and the evaluation results are shown in Table 5.

[0103] Table 1 Composition and physicochemical properties of the catalysts obtained in each example

[0104]

[0105]

[0106] Table 2 Composition and physicochemical properties of the catalysts obtained in each comparative example

[0107] Composition, wt% Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Specific surface area, m 2 / g]]> 40 38 130 43 Pore ​​volume, ml / g 0.15 0.18 0.79 0.16 Average pore size, nm 12 18 24 15 Bulk density, kg / L 145 95 81 85 Mechanical strength, N / particle 100 65 20 25

[0108] Table 3 Process conditions

[0109] raw material Dimethyl maleate Reaction temperature / ℃ 220 <![CDATA[Liquid hourly space velocity / h -1 > 0.6 Reaction pressure / MPa 6 Hydrogen ester molar ratio 200

[0110] Table 4 Activity evaluation results of the catalysts obtained in each example

[0111]

[0112]

[0113] Table 5 Activity evaluation results of the catalysts obtained in each comparative example

[0114] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Running time, h 500 500 500 500 Product composition, wt% γ-Butyrolactone 87.13 73.31 1.52 83.68 Dimethyl succinate 0.48 5.09 98.48 0.70 1,4-Butanediol 7.38 7.05 0 9.70 Tetrahydrofuran 2.09 9.01 0 4.36 n-Butanol 0.78 2.10 0 0 Acetal 2.14 3.44 0 1.56

[0115] The embodiments described in the present invention are merely detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments. That is, the present invention can be implemented independently of the steps described in the above embodiments. In summary, any improvements made by those skilled in the art to the present invention, as long as they do not depart from the content of the technical solutions of the present invention, and any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention, are within the scope of protection and disclosure of the present invention.

Claims

1. A catalyst for preparing γ-butyrolactone by hydrogenating dimethyl maleate, wherein: The catalyst has a core-shell structure, with the core being Cu-AO and the shell being MO-B, wherein A is an additive selected from one or more of Zn, Mn, Ba, Mg, Ti, Ge, Zr, and Cr; M is an active metal component selected from one or more of Pd, Ni, Pt, Au, and Ag; and B is a carrier component.

2. The catalyst according to claim 1, characterized in that The bulk density of the catalyst is 100-150 kg / L, preferably 120-150 kg / L; and / or the mechanical strength of the catalyst is 80-150 N / particle, preferably 105-150 N / particle.

3. The catalyst according to claim 1, characterized in that The catalyst is a spherical particle with a particle size of 0.5 to 7.0 mm, preferably 0.8 to 3.5 mm; and / or, in the catalyst, the shell thickness accounts for 5% to 30% of the catalyst particle radius, preferably 10% to 15%.

4. The catalyst according to claim 1, characterized in that In the catalyst, the core is Cu-AO, and A, calculated as oxide, accounts for 10% to 70% of the mass of Cu, calculated as oxide, preferably 30% to 50%; and / or, in the catalyst, the shell is MO-B, and M, calculated as oxide, accounts for 0.1% to 2.0% of the mass of B, preferably 0.5% to 1.0%.

5. The catalyst according to claim 1, characterized in that In the catalyst, B is a carrier component, preferably selected from one or more of alumina, activated carbon, and silica.

6. The catalyst according to claim 1 or 5, characterized in that In the catalyst shell layer, the pore diameter of the support component is 10 to 40 nm, preferably 13 to 25 nm.

7. A method for preparing the catalyst according to any one of claims 1 to 6, comprising: (1) Mixing the core raw material powder and the first binder into a wet ball, (2) mixing the shell raw material powder with the second binder and coating the wet ball obtained in step (1); (3) The material obtained in step (2) is allowed to stand in the presence of water vapor, and then dried and calcined to obtain a catalyst.

8. The method according to claim 7, characterized in that In step (1), the particle size of the core raw material powder is 60-200 mesh; and / or, in step (2), the particle size of the shell raw material powder is 150-300 mesh.

9. The method according to claim 7, characterized in that In step (1), the core raw material powder includes CuO and additive oxide, and the first binder is polyvinyl alcohol; and / or, in step (2), the shell raw material powder includes active metal oxide and carrier component, and the second binder is silicate cement powder; preferably, the added amount of the second binder accounts for 10% to 40% of the mass of the shell raw material powder.

10. The method according to claim 7, characterized in that The pelletizing method in step (1) is to use a powerful mixer for high-speed centrifugal granulation at a rotation speed of 1000 to 3000 rpm, preferably 2000 to 2500 rpm; the centrifugation time is 5 to 20 minutes, preferably 10 to 15 minutes; preferably, the particle size of the wet balls obtained in step (1) is 0.5 to 5.0 mm.

11. The method according to claim 7, characterized in that In step (2), the coating method can be a rolling ball method; preferably, in step (2), the coating thickness is 0.2 to 1.0 mm.

12. The method according to claim 7, characterized in that In step (3), the material obtained in step (2) is allowed to stand in the presence of water vapor under the following conditions: temperature of 100-150° C., preferably 120-130° C.; pressure of 0.3-0.8 MPa; and time of 1-10 hours, preferably 3-6 hours.

13. The method according to claim 7, characterized in that In step (3), the drying conditions are as follows: the drying temperature is 80-120° C., and the drying time is 4-10 hours; the roasting conditions are as follows: the roasting temperature is 300-700° C., and the roasting time is 3-8 hours.

14. Use of the catalyst according to any one of claims 1 to 6 in the hydrogenation of dimethyl maleate to produce γ-butyrolactone.

15. The use according to claim 14, characterized in that The application process is as follows: dimethyl maleate is contacted with the catalyst in the presence of hydrogen to react to obtain the product γ-butyrolactone; preferably, the reaction conditions are as follows: reaction temperature is 200-240°C, reaction pressure is 1.0-7.0 MPa, hydrogen-ester molar ratio is 100-500:1, liquid hourly volume space velocity is 0.1-1.0h -1 .

Citation Information

Patent Citations

  • Dimethyl maleate hydrogenation reaction catalyst as well as preparation method and application thereof

    CN113731442A